PERBANDINGAN PEMIKIRAN MUHAMMAD ABDUH DAN RASYID RIDHA TENTANG PENDIDIKAN - Nasrudin Yusuf (Lembaga penelitian dan pengabdian kepada Masyarakat, 2011)
Study About Education compare Thinking Abduh's Muhammad and Rasyid Ridha it mengasikan, unique, pull and has urgenitas alone, evenless dikritisi, dianalisis and than among Abduh's Muhammad thinking and Rasyid Ridha. Two laid pembaru Figure Islamic teaching basic principles is next they describe for dikinikan, actualized and diimplikasikan divides to universalize education. It, intent to discard black cloud that robe Islam people. Are not excessive, Abduh's muhammad and Rasyid Ridha's student was successful issue Islam people of stocks still thinking making for dynamic. IDE and their idea that bernas and diamond for upturned world education, now got takes in changing and new clarification for Islam states, including Republic Of Indonesia. its glorious contribution it, got take in resuscitation as spirit of Islamic people as it were ideally.